2016
DOI: 10.1080/10837450.2016.1193193
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the aqueous solubility and permeability of a poorly water soluble drug ritonavir via lyophilized milk-based solid dispersions

Abstract: In the present study, a lyophilized milk-based solid dispersion (SD) of ritonavir (RTV) was developed with the goal of improving its aqueous solubility. The SD was prepared by lyophilization, and characterized for its physicochemical and functional properties. Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), photomicroscopy and powder X-ray diffraction (PXRD) were used to confirm the formation and robustness of the SD formulation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…The zeta potential value (-22.35 ± 0.30 mV) obtained for APLC was greater than -30 mV, which indicates excellent stability of the APLC from flocculation when seen in the context of its low particle size. The zeta potential with range (-20 to 30 mV) was earlier demonstrated as a characteristic property of zeta potential for attraction followed by flocculation exceeding repulsion forces (Dhore et al, 2016;Freitas and Müller, 1998). The zeta potential value depends on the type and composition of phospholipids.…”
Section: Particle Size Analysis and Zeta Potentialmentioning
confidence: 99%
“…The zeta potential value (-22.35 ± 0.30 mV) obtained for APLC was greater than -30 mV, which indicates excellent stability of the APLC from flocculation when seen in the context of its low particle size. The zeta potential with range (-20 to 30 mV) was earlier demonstrated as a characteristic property of zeta potential for attraction followed by flocculation exceeding repulsion forces (Dhore et al, 2016;Freitas and Müller, 1998). The zeta potential value depends on the type and composition of phospholipids.…”
Section: Particle Size Analysis and Zeta Potentialmentioning
confidence: 99%
“…Tris-maleate buffer (50 mM, pH 6.5) was used for the digestions and was prepared by dissolving 11.86 g of Trizma-maleate, 0.74 g of calcium chloride dihydrate (5 mM), and 8.77 g of sodium chloride (150 mM) in water to a total volume of 1000 mL. Calcium chloride was added to remove the free fatty acids from the lipolysis medium that could inhibit lipolysis and to more closely resemble in vivo conditions where the free fatty acids are absorbed [3]. The pH stat component of the lipolysis model provides an indication of the kinetics of the lipolysis reaction by monitoring the addition of sodium hydroxide in response to production of the fatty acids to maintain a constant pH (6.5 in these studies).…”
Section: Methodsmentioning
confidence: 99%
“…The fat content in mammalian milk comprises over 95% triglycerides [1]. The recognition that these milk lipids can offer a solubilising environment for poorly water-soluble lipophilic drugs has led to a range of studies focusing on the solubility of drugs in milk [[2], [3], [4], [5], [6]] and in a limited number of studies the effect of milk on in vivo absorption and bioavailability [[7], [8], [9]]. The solubility of drugs in milk has been reported to be enhanced compared to that in aqueous media without fat present and in limited in vivo studies consequent increases in systemic exposure have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…A lyophilized milk-based solid dispersion was developed to enhance the solubility and permeability of ritonavir. 31 Ritonavir was dispersed in an amorphous polymer matrix and existed primarily in a molecularly dispersed state. 32 This formulation (drug:carrier mass ratio of 1:4) exhibited higher dissolution efficiency (~55.26 ± 1.29%, representing a 10-fold increase compared to pure ritonavir).…”
Section: Preparing Solid Dispersionmentioning
confidence: 99%